The Effect of Web-Based Education on Mother’s Knowledge and Attitudes in Stunting Prevention - Andayani, Sri Astutik; Hasim, Ely; Chandra Dewi, Novela Eka (Universitas Padjadjaran, 2024)
Stunting incidents are often not realized due to chronic nutritional problems which can be caused by the mother's lack of knowledge in providing food intake that is appropriate to her child's nutritional needs. Currently, the use of technology continues to increase. This research was carried out by using technology that is currently developing, namely using media. website-based social. This research aims to determine the effect of web-based education on mothers' knowledge and attitudes in efforts to prevent stunting. This research used a quasi-experimental method with a pre-test and post-test control group approach, 44 respondents were selected based on the lemeshow formula sampling technique. The instrument used in this research used a questionnaire. Bivariate data analysis used the Wilcoxon test and Mann Whitney test. The results of this study showed that the level of knowledge of mothers in the intervention group was 0.000 and in the control group 0.108. Meanwhile, the results of research attitudes with a significant value in the intervention group were 0.000 and the control group was 0.216. Meanwhile, the difference in knowledge scores between the intervention group and the control group was 0.028 and the difference in attitude scores between the intervention group and the control group was 0.001. There were significant differences in the level of knowledge and attitudes in the intervention group and the control group. The conclusion from the research is that there is an influence of web-based education on mothers' knowledge and attitudes in efforts to prevent stunting in the intervention group.